Surface tension and oscillation of water droplet under microwave radiation - Asada, M.; Kanazawa, Y.; Asakuma, Y.; Honda, I.; Phan, Chi (2015)
© 2015 The Institution of Chemical Engineers. Surface tension of fluids is an important factor controlling multiphase systems and is often manipulated by surfactants during industrial processes. Previously, we have found that water surface tension was reduced under continuous microwave irradiation. The reduction was not explainable by thermal effects. The new insights can lead to important application of microwaves in multiple-phase systems. In this study, effect of various microwave irradiation modes on surface tension of water was investigated. The surface tension reduction was confirmed for pulsed microwave irradiation. The reduction varied with the applied power as well as interval between irradiations. The droplet oscillation and internal convection were also investigated during and after microwave irradiation to clarify the mechanism. It was found that the convection within the water droplet was proportional to the microwave power. In contrast, the frequency of oscillation was independent on the microwave power. These results on surface tension, oscillation and convection will provide important insights for designing microwave applications.